Tax indiscipline in Morocco: In search of compromise - BAHOUSSA , Abdelaziz; BAYCHOU , Youssef; RGUITI , EL Mehdi (Revue du contrôle, de la comptabilité et de l’audit, 2022)
A fair tax is above all a tax that is recognized as fair by both parties (the administration and the taxpayer), and this question is at the heart of the relationship between the individual and the State. Our contribution of a theoretical nature aims to review a synthesis on first the behaviors of tax indiscipline, then the different forms of this event, then its impact on the resources of the State and finally the solutions and recommendations proposed to reduce the phenomenon and promote the role of the administration in raising awareness of taxpayers in terms of tax citizenship, as well as compliance with tax laws in force. Among the topics to recognize that the management of the risk of tax indiscipline is a major concern for the tax authority. This management is of course based on a risk analysis based on the incidents already experienced by the tax administration. These risks may be internal (such as the poor management of the data processing tools available to the administration, as well as the low rate of collection of tax revenues, and the errors and omissions that may be committed, the abuse of rights that the administration may practice), then external risks (particularly the legislative and regulatory framework), and finally specific risk management strategies will, where appropriate, make it possible to reduce these risks as much as possible. The study carried out, based on the questionnaire method, among 50 individuals and legal entities of private law, allowed us to analyze the tax behavior of a representative sample of taxpayers, as developed below. The initial objective was to collect the different opinions, reflections and self-judgment of our target about tax indiscipline.